Evaluation of Airway Scope at Improving the Success Rate of the First Intubation Attempt by Nonexpert Physicians: A Randomized Crossover Manikin Study. (20th November 2012) - Yuasa, Haruyuki; Yokoyama, Hiroyuki; Yonemoto, Naohiro; Kasahara, Yoichiro; Nonogi, Hiroshi
Abstract : Purpose . The aim of the study was to assess the performance of Airway Scope (AWS) on the first attempt at intubation in manikins by nonexpert physicians. Methods . A randomized crossover trial involving seven scenarios. Participants: residents of a cardiovascular hospital. In group A, the AWS procedure was performed first followed by Machintouch Laryngoscopy (ML), while in group B the ML procedure was performed first and then the AWS. The primary outcome assessed was the success of first intubation attempt in a normal scenario. The secondary outcome assessments were success in six other scenarios, and also elapsed time and dental trauma caused in all scenarios. Results . There were 34 participants. All AWS-assisted intubations were successfully completed, but one ML-assisted intubation failed in the normal scenario (P = 0.32 ). The outcomes achieved by the AWS in scenarios involving cervical immobilization (P = 0.03 ), tongue edema (P ≤ 0.001 ), pharyngeal obstruction (P ≤ 0.001 ), and jaw trismus (P = 0.001 ) were superior to those obtained with the ML. Conclusions . Use of AWS-assisted intubation in manikin scenarios results in a significantly high intubation success rate on the first attempt by nonexpert physicians. These findings suggest this new device will be useful for nonexpert physicians in emergency situations.